SFC Stock-Flux Consistent Model in post-Keynesian thought - Zenagui, Sidahmed (Finance and Business Economies Review, 2019)
This paper is a detailed analysis of the SFC paradigm in the Post-Keynesian thought by Lavoie and Godley (2001-2002), based on cash flows between macroeconomic clusters in the form of an input and output matrix among the components of the real economy, (Households, Enterprises, banks) as a basic model. Whose ideas did Dos Santos and Zezza (2004) by from to merging other sectors, within the same closed economy by adding the central bank and the government, How Zezza (2008) tried to explain the crisis of the United States in 2008, expand.